Vogt-Koyanagi-Harada Disease and Birdshot Retinochoroidopathy, Similarities and Differences: A Glimpse into the Clinicopathology of Stromal Choroiditis, a Perspective and a Review - Elahi, Sina; Herbort, Carl P., jr. (Klinische Monatsblätter für Augenheilkunde, 2019)
The purpose of this work was to give a comprehensive and updated review on two primary stromal choroiditis entities, Vogt-Koyanagi-Harada disease (VKH) and birdshot retinochoroiditis (BRC). Their appraisal has become much more precise thanks to new investigational methods, such as indocyanine green angiography (ICGA) and enhanced depth imaging optical coherence tomography (EDI-OCT), which give substantially improved imaging access to the choroid. In this review, we focus on the crucial changes brought by this progress in the understanding, diagnosis, and management of these disorders. Application of these methods makes it possible to reach an early diagnosis, therefore allowing early treatment, which has led to a profound improvement in outcomes when compared to previous management.
Keywords: birdshot retinochoroiditis; Vogt-Koyanagi-Harada disease; stromal choroiditis; indocyanine green angiography; immunosuppressive therapy